The role of modern technologies in Promoting scientific geographic research with reference to the Internet and geographic information systems (GIS) - Mohamed, Amel Elmahi Elkhlifa (Journal of natural sciences, life and applied sciences, 2021)
This is the era of technology that is nictitated everyone to adopt with this age and does not participate actively in the successive developments of scientific discoveries and technological innovations will have no presence in it, where the power of science and technology, and the word for those who have the cornerstone of technical development, so must To include technical literacy dimensions in formal and non-formal education programs in order to achieve technical enlightenment for all, in particular scientific research.The aim of the research is to shed light on the impact of modern technologies on the development of scientific research, especially the Internet, geographic information systems, encouraging faculty members and graduate students to use modern techniques in scientific research, and to highlight the positive aspects which are encouraging reasons for the use of modern technologies in scientific research. For this purpose, the descriptive analytical approach was usedThe importance of modern technologies in providing time and effort of the researcher, the multiplicity of sources of electronic information between the center used to the substantive coverage, the expansion of electronic publishing and varied between the periodicals, books, magazines, manuals, dictionaries and dictionaries, so the research recommended the need to develop the infrastructure of technology, Cooperation between the relevant authorities to reach the maximum benefit.
Keywords: modern technologies; scientific research; internet; geographic information systems (GIS)